Implementation of complete basic vaccination among low-income families participating in Indonesian social assistance programs - Fadillah Salwa; Fitriani Pramita Gurning (JOURNAL OF Medical Surgical Concerns, 2026)
Background: Complete basic vaccination is essential for achieving optimal child health outcomes and preventing vaccine-preventable diseases. Despite Indonesia's national vaccination program mandating complete basic vaccination for children, particularly among Indonesian social assistance programs or Program Keluarga Harapan (PKH) recipients, coverage remains suboptimal. In Medan City, complete basic vaccination coverage at Community Health Centers reached only 76.9% in 2024, falling short of the 80% national target, indicating significant gaps in program implementation. Purpose: To analyze the determinants of complete basic vaccination implementation among low-income families enrolled in Indonesian social assistance programs. Method: A sequential exploratory mixed methods design was employed. Qualitative data were obtained through in-depth interviews with two key informants (health center coordinator and vaccination officer), while quantitative data were collected from 50 social assistance program recipient mothers using structured questionnaires assessing knowledge, family support, and vaccination completion status. Data analysis included thematic analysis for qualitative data and descriptive statistics for quantitative data, with chi-square tests employed to examine associations between determinants and vaccination outcomes. Results: Among social assistance program recipient mothers, 56% demonstrated adequate knowledge of vaccination standards, while 48% reported receiving adequate family support. Policy implementation showed high compliance with national guidelines; however, resource constraints were identified, including limited facilities at 40% of posyandu sites and insufficient vaccinator training. Inter-organizational communication challenges were evident in cross-sectoral data collection and target mobilization. Conclusion: Maternal knowledge and family support were identified as significant determinants of complete basic vaccination among social assistance program recipients. Achieving national vaccination targets requires strengthening health education programs, enhancing family engagement strategies, improving cross-sectoral coordination, and ensuring adequate facility infrastructure and personnel training in resource-limited settings.